KBG syndrome in two patients from Egypt. Issue 6 (28th March 2020) - Sayed, Inas S. M.; Abdel‐Hamid, Mohamed S.; Abdel‐Salam, Ghada M.H.
Abstract: KBG syndrome is an intellectual disability (ID) associated with multiple congenital anomalies in which the macrodontia could be the clue for the diagnosis. It is caused either by heterozygous variant in ANKRD11 gene or 16q24.3 microdeletions that involve the ANKRD11 gene. Here, we report on two unrelated male patients who presented with ID, short stature, webbing of neck, and cryptorchidism. Noonan syndrome was suspected first but the presence of macrodontia in both patients pointed to KBG syndrome which was confirmed thereafter by the identification of a novel pathogenic variant in ANKRD11 gene, c.5488G>T (p.E1830*). Macrodontia was noticed in all the deciduous anterior teeth in Patient 1. This observation was reported previously in few patients, but it seems to be a common feature that could be misdiagnosed as premature eruption of teeth. Therefore, our results confirm that maxillary permanent central incisors may not be the only teeth affected in KBG but also all the deciduous teeth. Interestingly, desquamative gingivitis was additionally noted in Patient 1, which has not been reported previously, however; it could be a coincidental finding. To the best of our knowledge, this is the first report from Egypt.